Ultraviolet light in food technology : principles and applications - Koutchma, Tatiana N. (CRC Press, Taylor & Francis Group, 2019)
UV light is one of a number of emerging non-thermal food processing technologies that can be used in a broad range of applications producing food products with longer shelf-life, more safe, and with higher nutritional quality. The new edition of Ultraviolet Light in Food Technology: Principles and Applications will present recent understanding of the fundamentals of UV light along with new applied knowledge that has accumulated during the 7 years since the first edition published in 2009. The new edition of the book will have 11 chapters including 2 new chapters--on chemical destruction with UV light and food plant safety--along with 6 chapters greatly expanded and updated.
Keywords: Radiation preservation of food.; Ultraviolet radiation.; elektronické knihy; electronic books